APPLICATION OF DISCOVERY LEARNING LEARNING MODEL TO CLASS X HIGH SCHOOL STUDENTS IN THE MATERIAL “TEKS ANEKDOT” - Mustofa, Mustofa; ariyanti, firda aulia (EDU-KATA, 2024)
In language learning, one of the texts used is anecdotal text. This research uses a descriptive approach to improve students' knowledge and skills on anecdotal text material. Learning by using the discovery learning method can increase students' knowledge of anecdotal text and improve students' ability to write anecdotal text.